Nitrogen Isotopes in the Atlantic and Pacific Oxygen Minimum Zones - Ryabenko, Evgenia (2011)
As a limiting element for biological productivity, nitrogen occupies a central role in ocean biogeochemistry. It exists in more chemical forms than most other elements, with a myriad of chemical transformations that are unique to this element. Nearly all these transformations are undertaken by marine organisms as part of their metabolism, which involves isotopic fractionation. Thus stable isotopes of nitrogen carry important information on sources and sinks of nitrogen and its transformation within the oceanic cycle. This dissertation focused on the nitrogen cycle in two very different ocean regions: the Eastern Tropical North Atlantic and the Eastern Tropical South Pacific. These two basins are associated with Oxygen Minimum Zones (OMZs), which have a great influence on the global nitrogen cycle. The first part of the thesis describes the method used for nitrogen isotope measurement. The method was used to contrast the two OMZs, to investigate what processes are dominating in each of them and how they influence the global nitrogen cycle. The nitrogen cycle in the Atlantic OMZ is dominated by nitrification and dust deposition, which could be detected in nitrogen isotope (δ15N) signatures. In the Pacific OMZ, effects of nitrogen loss processes were most pronounced. The nitrogen fractionation factor, however, was much smaller than expected (11.4 ‰ instead of 20 – 30‰), which was most probably was an effect of denitrification in sediments. The last two parts are devoted to the Pacific OMZ nitrogen cycle. δ15N in water column and surface sediments showed a parallel latitudinal increase from north to south along the Peru margin, which correlates with intensification of the OMZ. From water column data it was showed that N-loss processes indirectly influence the δ15N found in the surface sediments (δ15Nsed). Latitudinal distribution of δ15Nsed along the South American coast, however, showed a very good correlation with surface water nitrogen utilization, outshining N-loss processes. [.] Stickstoff nimmt als ein ...